Объяснение:
[tex]\frac{(3^4)^2*2^{11}}{4*36^4} =\frac{3^8*2^{11}}{2^2*(6^2)^4} =\frac{3^8*2^9}{6^8}=\frac{3^8*2^8*2}{6^8}=\frac{(3*2)^8*2}{6^8}=\frac{6^8*2}{6^8} =2.[/tex]
Решение.
Применяем свойства степеней : [tex]\bf (a^{n})^{m}=a^{n\cdot m}\ ,\ (a\cdot b)^n=a^{n}\cdot b^{n}[/tex] .
[tex]\bf \dfrac{a^{n}}{a^{m}}=a^{n-m}[/tex] .
[tex]\bf \dfrac{(3^4)^2\cdot 2^{11}}{4\cdot 36^4}=\dfrac{3^8\cdot 2^{11}}{2^2\cdot (6^2)^4}=\dfrac{3^8\cdot 2^{11}}{2^2\cdot 6^8}=\dfrac{3^8\cdot 2^{11}}{2^2\cdot (2\cdot 3)^8}=\dfrac{3^8\cdot 2^{11}}{2^2\cdot 2^8\cdot 3^8}=\dfrac{2^{11}}{2^{10}}=2[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Объяснение:
[tex]\frac{(3^4)^2*2^{11}}{4*36^4} =\frac{3^8*2^{11}}{2^2*(6^2)^4} =\frac{3^8*2^9}{6^8}=\frac{3^8*2^8*2}{6^8}=\frac{(3*2)^8*2}{6^8}=\frac{6^8*2}{6^8} =2.[/tex]
Решение.
Применяем свойства степеней : [tex]\bf (a^{n})^{m}=a^{n\cdot m}\ ,\ (a\cdot b)^n=a^{n}\cdot b^{n}[/tex] .
[tex]\bf \dfrac{a^{n}}{a^{m}}=a^{n-m}[/tex] .
[tex]\bf \dfrac{(3^4)^2\cdot 2^{11}}{4\cdot 36^4}=\dfrac{3^8\cdot 2^{11}}{2^2\cdot (6^2)^4}=\dfrac{3^8\cdot 2^{11}}{2^2\cdot 6^8}=\dfrac{3^8\cdot 2^{11}}{2^2\cdot (2\cdot 3)^8}=\dfrac{3^8\cdot 2^{11}}{2^2\cdot 2^8\cdot 3^8}=\dfrac{2^{11}}{2^{10}}=2[/tex]